Bioactive Lupane and Hopane Triterpenes from Lepisanthes senegalensis - Lomchid, Pornwimon; Nasomjai, Pitak; Kanokmedhakul, Somdej; Boonmak, Jaursup; Youngme, Sujittra; Kanokmedhakul, Kwanjai (Planta Medica, 2017)
Two lupane and hopane caffeates (1 and 4) and two hopane coumarates (2 and 3) along with eight known compounds (5–12) were isolated from stems and roots of Lepisanthes senegalensis. Their structures were established on the basis of spectroscopic techniques. The structure of compound 2 was confirmed by single-crystal X-ray diffraction analysis. Triterpenes 1 and 4–6 showed cytotoxicity against the NCI-H187 cell line with IC50 values of 31.5, 28.5, 16.2, and 4.0 µM, respectively. However, these compounds also showed cytotoxicity against Vero cells, with IC50 values of 75.5, 16.6, 8.9, and 5.0 µM, respectively. In addition, compound 6 exhibited a moderate antimalarial activity with an IC50 value of 4.5 µM.
Keywords: Lepisanthase senegalensis; Sapindaceae-triterpene caffeate; hopane coumarate-antimalarial; cytotoxicity